Clinical study of post partum eclampsia in a tertiary care hospital - Bharathi, R.; Mohana Sundari, K. P.; Deeba Jayanthi, R. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The study was done to analyze epidemiological factors associated with postpartum eclampsia and to assess the maternal outcome. Methods: This is a retrospective study done in a tertiary care hospital, Govt. Mohan Kumaramangalam Medical College Hospital, Salem, Tamil Nadu between Jan 2015 to Dec 2015. Case records of all the postpartum eclampsia patients admitted during this period were analyzed. Results: This study showed that the incidence of postpartum eclampsia in our hospital was 9.3 per 1000 deliveries. It is more common in the age group of 21 - 25 years (52%) and frequent occurrence in primi para (50.7%). Commonest mode of delivery was vaginal route (63%). The occurrences of seizures were common between 48 hours to 7 days (30.7%). The mortality was 6 (10.7%) out of 56 maternal deaths that occurred during the study period. Conclusions: Postpartum eclampsia is still one of the most common obstetric emergencies which have a significant role in maternal mortality. Regular antenatal care alone is not enough; they also need regular postnatal follow up care and health education.